1999
DOI: 10.1117/12.349668
|View full text |Cite
|
Sign up to set email alerts
|

<title>Artificial muscles working in aqueous solutions or in air</title>

Abstract: Macroscopic electrochemomechanicaldevices formed by bilayers or triple layers between electroactive polymers and a non conducting, adherent and flexible poplymer, able to describe angular movements in liquid electrolytes under electrochemical control are presented. Using a polymeric electrolyte, able to conduct ions, sandwiched between two polypyrrole layers, a muscle working in air was constructed. Any of those devices work under electrochemical control of the conformational changes occuring in polymeric chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This causes the actuator to bend [216,221,227,228]. In a later work, three-layer actuators were presented, which have layers of PPy on both sides of a flexible middle layer [229][230][231]. Figure 13 gives an impression of both structures and their corresponding reaction mechanisms.…”
Section: Current Research Efforts and Textile Applicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…This causes the actuator to bend [216,221,227,228]. In a later work, three-layer actuators were presented, which have layers of PPy on both sides of a flexible middle layer [229][230][231]. Figure 13 gives an impression of both structures and their corresponding reaction mechanisms.…”
Section: Current Research Efforts and Textile Applicationsmentioning
confidence: 98%
“…Later, they also successfully performed experiments with solid electrolytes. They found that, as long as the solid electrolyte provides the same amount of electrical energy as the liquid one, the feasible radius of movement is identical [230,231].…”
Section: Current Research Efforts and Textile Applicationsmentioning
confidence: 99%
“…Moreover, bending artificial muscles, developed as multi-(bi-or three-) layer devices [15][16][17][18][19][20][21], have then been studied and have presented unique actuating and sensing abilities. Indeed, as for any other electrochemical, or chemical, reaction, the reaction rate is influenced by working temperatures or reactant concentrations.…”
Section: Introductionmentioning
confidence: 99%